2005
DOI: 10.1161/circulationaha.105.534180
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Fetal Pulmonary Venous Flow Patterns in Identifying the Need for Atrial Septoplasty in the Newborn With Hypoplastic Left Ventricle

Abstract: Background-Pulmonary venous Doppler (PVD) flow patterns in the fetus with hypoplastic left heart syndrome (HLHS) have been correlated with restrictive interatrial communication or intact atrial septum (RAS) postnatally; however, the ability of PVD to identify the neonate requiring emergent atrial septoplasty (EAS) for severe left atrial hypertension and hypoxemia has not been critically evaluated. It was the purpose of this study to determine the predictive power of fetal PVD in identifying the need for EAS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(80 citation statements)
references
References 32 publications
(57 reference statements)
4
73
1
2
Order By: Relevance
“…Fetal Doppler assessment of pulmonary venous flow patterns can aid in gauging the degree of impediment to left atrial egress, with greater prominence of flow reversal during atrial contraction reflecting greater restriction. 176,177,481 Assessment of pulmonary arterial impedance through Doppler imaging during maternal hyperoxygenation can test for pulmonary vasoreactivity in the fetus with HLHS. A diminished vasoreactive response to maternal hyperoxygenation suggests an abnormal pulmonary vasculature and indicates clinically important restriction at the foramen ovale.…”
Section: Hlhs With Restrictive or Intact Atrial Septummentioning
confidence: 99%
See 1 more Smart Citation
“…Fetal Doppler assessment of pulmonary venous flow patterns can aid in gauging the degree of impediment to left atrial egress, with greater prominence of flow reversal during atrial contraction reflecting greater restriction. 176,177,481 Assessment of pulmonary arterial impedance through Doppler imaging during maternal hyperoxygenation can test for pulmonary vasoreactivity in the fetus with HLHS. A diminished vasoreactive response to maternal hyperoxygenation suggests an abnormal pulmonary vasculature and indicates clinically important restriction at the foramen ovale.…”
Section: Hlhs With Restrictive or Intact Atrial Septummentioning
confidence: 99%
“…175,176,481,547,572,584,585,[588][589][590][591][592][593][594] Fetuses with HLHS identified to have a severely restrictive or intact atrial septum are at increased risk for compromise in the delivery room if fetal pulmonary vein flow shows significant reversed flow suggesting severe left atrial hypertension in the third trimester. 175,176,481,549,572 In 2 studies, 176,481 the ratio of pulmonary vein forward to reversed velocity-time integral was used to determine potential need for intervention. These studies suggest that a ratio <3 is predictive of an increased likelihood of needing emergent opening of the atrial septum by catheterization or surgery and therefore should prompt delivery room management to include immediate access to a cardiac team for the procedure if it is indicated.…”
Section: Foramen Ovale-dependent Lesionsmentioning
confidence: 99%
“…Very importantly, there were no differences in any of the variables evaluated between both hospitals. The median GA at diagnosis was 22.0 weeks (range, 20-30.3) and at intervention was 23.0 [20][21][22][23][24][25][26][27][28][29][30][31][32]. The majority of fetuses showed reversed flow at the aortic arch and/or monophasic MV inflow as well as mitral regurgitation, left-to-right interatrial shunt, and moderate or severe LV systolic dysfunction (11/28, 39.3%, and 14/28, 50.0%, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…LV systolic function was classified according to the ejection fraction into normal ( ≥ 55%), mildly abnormal (45-54%), moderately abnormal (30-44%), and severely abnormal (<30%) [20] . The flow at the aortic arch and foramen ovale was systematically assessed with color Doppler, and a detailed survey of flow waveforms in the pulmonary veins was undertaken to identify a restrictive interatrial communication [21] . Endocardial fibroelastosis (EFE) was graded as 0, none; 1, mild (scattered echogenic dots in the LV); 2, moderate (noncontiguous echogenic patches throughout the LV); and 3, severe (contiguous echogenic lining of the LV) [22] .…”
Section: Methodsmentioning
confidence: 99%
“…For example, damage such as vascular dysplasia and macrovascular dysplasia may occur due to abnormal hemodynamics during the fetal period, resulting in severe pathological changes, including single ventricle defects and severe heart dysfunction, occurring, which may lead to mortality (5)(6)(7)(8)(9). In particular, previous studies have identified severe coarctation of the aorta or aortic atresia, causing dysplasia of the aortic arch or left ventricle (7); pulmonary atresia or tricuspid atresia with an intact ventricular septum, resulting in right ventricular dysplasia; Ebstein's malformation of the tricuspid valve, resulting in functional pulmonary atresia (6); and severe damage to the vascular bed of the fetal lung as forms of secondary damage (5,8,9). These may be avoided by in utero correction of primary defects, which may potentially preserve fetal development (10).…”
Section: Introductionmentioning
confidence: 99%